Monocular meta-imaging camera sees depth - Yujin Liu; Xueli Chen (Light: Science & Applications)
Abstract A novel monocular depth-sensing camera based on meta-imaging sensor technology has been developed, offering more precise depth sensing with millimeter-level accuracy and enhanced robustness compared to conventional 2D and light-field cameras.